Methodological Framing of a Case Born from the Contemporary Clown - Vieira, Hugo Américo (2017)
This article aims at approaching the issue and the methodological strategy of an investigation project “in progress”, which has as the main vertebral spine “the clown”. The “hearing” is the main topic of the character construction to be created by laboratorial creative processes with others, followed by the investigator’s artistic work in the elaboration of a show, which will be the object of the thesis. This clown will summon other areas such as yoga, kung-fu, dance-theatre, and will be supported by Bogart’s viewpoints technique. On inserting ourselves in a qualitative investigation paradigm I am entering the methodological issue with some concerns regarding sensitivities. This study focuses strongly on the a/r/ tographic contour, which lays “in-between” spaces of theory, praxis and creation. Therefore in this article I try to enlightenissues within these pertinences corresponding to issues involving feelings, laboratory and the character in the creative process and more precisely in this project.